Survival outcomes after delayed cytoreduction surgery following neoadjuvant chemotherapy in advanced epithelial ovarian cancer. Issue 12 (29th October 2020) - Yao, Shih-Ern; Tripcony, Lee; Sanday, Karen; Robertson, Jessica; Perrin, Lewis; Chetty, Naven; Land, Russell; Garrett, Andrea; Obermair, Andreas; Nascimento, Marcelo; Tang, Amy; Jagasia, Nisha; et al.
Abstract : Objective: Interval cytoreduction following neoadjuvant chemotherapy is a well-recognized treatment alternative to primary debulking surgery in the treatment of advanced epithelial ovarian cancer where patient and/or disease factors prevent complete macroscopic disease resection to be achieved. More recently, the strain of the global COVID-19 pandemic on hospital resources has forced many units to alter the timing of interval surgery and extend the number of neoadjuvant chemotherapy cycles. In order to support this paradigm shift and provide more accurate counseling during these unprecedented times, we investigated the survival outcomes in advanced epithelial ovarian cancer patients with the intent of maximal cytoreduction following neoadjuvant chemotherapy with respect to timing of surgery and degree of cytoreduction. Methods: A retrospective review of all patients aged 18 years and above with FIGO (2014) stage III/IV epithelial ovarian cancer treated with neoadjuvant chemotherapy and the intention of interval cytoreduction surgery between January 2008 and December 2017 was conducted. Overall and progression-free survival outcomes were analyzed and compared with patients who only received chemotherapy. Outcome measures were correlated with the number of neoadjuvant chemotherapy cycles and amount of residual disease following surgery. Results: Six hundred and seventy-one patients (median age 67 (range 20–91) years) were included in the study with 572 patients treated with neoadjuvant chemotherapy and surgery and 99 patients with chemotherapy only. There was no difference in the proportion of patients in whom complete cytoreduction was achieved based on number of cycles of neoadjuvant chemotherapy (2–4 cycles: 67.7%, n=337/498); ≥5 cycles: 62.2%, n=46/74). Patients undergoing cytoreduction surgery after neoadjuvant chemotherapy had a median 5-year progression-free and overall survival of 24 and 38 months, respectively. No significant difference in overall survival between surgical groups was observed (interval cytoreduction: 41 months vs delayed cytoreduction: 43 months, p=0.52). Those who achieved complete cytoreduction to R0 (no macroscopic disease) had a significant median overall survival advantage compared with those with any macroscopic residual disease (R0: 49–51 months vs R<1: 22–39 months, p<0.001 vs R≥1: 23–26 months, p<0.001). Conclusions: Survival outcomes do not appear to be worse for patients treated with neoadjuvant chemotherapy if cytoreduction surgery is delayed beyond three cycles. In advanced epithelial ovarian cancer patients the imperative to achieve complete surgical cytoreduction remains gold standard, irrespective of surgical timing, for best survival benefit.